ANALISIS MANAJEMEN BISNIS SYARIAH PERAN SALES PROMOTION GIRL TERHADAP PENINGKATAN PENJUALAN PERUSAHAAN - Rahman, Fitria Setia; Trihantana, Rully; Suryani, Ermi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The purpose of this research is to analyze Sharia Business Management. The Role of Sharia Sales Promotion Girls in Increasing Company Sales. The company in this case is Tokoh Amanah MM. This type of research is descriptive qualitative (field research). The data source used by researchers in this thesis is the results of analysis of interviews with informants (shop owners and sales promotion girls at Toko Amanah MM). The secondary data in this research are books, journals and the like. The final data used is tertiary data such as dictionaries, encyclopedias, internet and related. To obtain data from informants, researchers used data collection techniques with face-to-face interviews and Toko Amanah MM documentation. The data analysis technique in this research is inductive, namely based on certain facts, then analyzed until a general problem solution is found. Based on the results of research and search analysis carried out by researchers, Sales Promotion Girl's strategy in marketing Toko Amanah MM products is mobile selling. The Sales Promotion Girl's interaction at Toko Amanah MM is polite, friendly and smiles easily in selling products and transactions based on deliberative consensus transactions in accordance with Islamic law or the principles of muamalah or business in Islam. Another thing that plays a role in increasing sales of Toko Amanah MM is the Sales Promotion Girl's ability to know the products the store has, the level of intelligence in promoting products and skills in selling products well.